Social Support and Depressive Symptoms in the Context of COVID-19 Lockdown: The Moderating Role of Attachment Styles - Stefanella Costa-Cordella; Stefanella Costa-Cordella; Stefanella Costa-Cordella; Anastassia Vivanco-Carlevari; Anastassia Vivanco-Carlevari; Alejandra Rossi; Camilo Arévalo-Romero; Camilo Arévalo-Romero; Jaime R. Silva; Jaime R. Silva; Jaime R. Silva (Frontiers Media S.A., 2022)
Objectives: COVID-19 sanitary measures (social distancing, school closures) have deeply impacted social life, support networks, and their protective role in mental health. The present study aims to understand how attachment styles influence the way individuals experience social support. Particularly, investigating its moderating role in the relationship between social support and depression.Methods: An online survey was designed to clarify the role of adult attachment styles (ECR-S) in the perceived social support (MOSS) and self-reported depressive symptoms (BDI-SF) in the COVID-19 context.Results: Positive social interactions was the most important dimension of social support for lower depression symptoms. Individuals attachment strategies have a moderating role in the relation between of social support and depression. Crucially, insecure attachment style wanes the positive impact of social support in depression.Conclusion: Aligned with the existing literature, attachment security is an essential factor in our current understanding of relationships and mental health. Exploring specific and indivual attachment strategies might be a powerful tool to protect population's mental healt.